PtrA, Piz-t, and a novel minor-effect QTL (qBR12_3.3–4.4) collectively contribute to the durable blast-resistance of rice cultivar Tainung 84 - Sheng-Shan Wang; Wei-Bin Chang; Ming-Chien Hsieh; Szu-Yu Chen; Dah-Jing Liao; Ching-Ying Liao; Wei-Chiang Shen; Hong-Hua Chen; Chieh-Yi Chen; Yi-Chia Chen; Yueh-Lin Lin; Chih-Wei Tung; et al. (Botanical Studies)
Abstract Background Rice blast caused by Pyricularia oryzae is a major threat to rice production worldwide. Tainung 84 (TNG84) is an elite japonica rice cultivar developed through the traditional pedigree method. It has maintained superior blast resistance since its release in 2010. This study aimed to investigate the genetic factors underlying the durable resistance of TNG84 in Taiwan. Results Quantitative trait locus (QTL) mapping was conducted using 122 F2 individuals and F2:3 families derived from the cross of TNG84 and a susceptible japonica cultivar Tainan 11 (TN11). Using 733 single nucleotide polymorphisms (SNPs) obtained through genotyping-by-sequencing and three P. oryzae isolates (D41-2, 12CY-MS1-2, and 12YL-TT4-1) belonging to different physiological races and Pot2 lineages, a major QTL was identified in the region of 52–54 cM (9.54–15.16 Mb) on chromosome 12. Fine-mapping using 21 F5:6 recombinants delimited the QTL to a 140.4-kb region (10.78 to 10.93 Mb) containing the known resistance gene Ptr. Sequencing analysis indicated that TNG84 carries the resistant PtrA allele and TN11 carries the susceptible PtrD allele. Investigation of the Ptr haplotypes in 41 local japonica rice cultivars revealed that eight PtrA-containing cultivars (19.5%) consistently exhibited good field resistance in Taiwan from 2008 to 2024. Subsequently, a few F5:6 lines (P026, P044, P092, and P167) lacking the resistant Ptr allele were observed to exhibit a resistant phenotype against P. oryzae 12YL-TT4-1-lab. Trait-marker association analyses using eight F6:7 homozygous recombinants, 378 BC1F2 from P044 backcrossed to TN11, and 180 BC1F2 from P092 backcrossed to TN11, identified Piz-t on chromosome 6 and a new QTL located between 3.3 Mb and 4.4 Mb on chromosome 12 (designated as qBR12_3.3–4.4). Analysis of 12 selected BC1F2:3 lines derived from P044 demonstrated that in the absence of Ptr and Piz-t, qBR12_3.3–4.4 alone reduced the disease severity index from approximately 6.3 to 3.9. Conclusions PtrA is likely the primary gene responsible for the broad-spectrum and durable resistance of TNG84. Piz-t confers narrow-spectrum resistance, while qBR12_3.3–4.4 contributes partial resistance. The discovery of qBR12_3.3–4.4 has provided a new source of blast resistance, and the markers developed in this study can be utilized in future breeding programs.